2009
DOI: 10.1165/rcmb.2008-0148oc
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Asymmetric Dimethylarginine Alters Lung Function and Induces Collagen Deposition in Mice

Abstract: Increasing evidence suggests that lung mechanics and structure are maintained in part by an intimate balance between the L-arginine-metabolizing enzymes nitric oxide synthase (NOS) and arginase. Asymmetric dimethylarginine (ADMA) is a competitive endogenous inhibitor of NOS. The role of ADMA in the regulation of NOS and arginase in the airways has not yet been explored. Our objective was to investigate the role of ADMA in lung physiology. A murine model of continuous subcutaneous ADMA infusion via osmotic mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 67 publications
3
91
0
Order By: Relevance
“…Greiss reagents (1% sulfanilamide and 0.1% napthylethylenediamine in 5% phosphoric acid; Ricca Chemical, Pocomoke, MD) were used to measure the nitrite concentrations in the lavage fluid (WT, n ¼ 9-15; DDAH Tg, n ¼ 9) as previously described (Wells et al, 2009). Calibration curves were made with NaNO 2 (Sigma) dissolved in PBS.…”
Section: Measurement Of Nitrite Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greiss reagents (1% sulfanilamide and 0.1% napthylethylenediamine in 5% phosphoric acid; Ricca Chemical, Pocomoke, MD) were used to measure the nitrite concentrations in the lavage fluid (WT, n ¼ 9-15; DDAH Tg, n ¼ 9) as previously described (Wells et al, 2009). Calibration curves were made with NaNO 2 (Sigma) dissolved in PBS.…”
Section: Measurement Of Nitrite Concentrationsmentioning
confidence: 99%
“…L-Arginine deficiency leads to uncoupling of NOS and oxidant formation (Boger et al, 2000;. It is established that elevated ADMA contributes to endothelial dysfunction (Raptis et al, 2014), pulmonary inflammation (Klein et al, 2010), and fibrosis (Wells et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated a potential contribution of imbalances in L-arginine metabolism to the development of airway hyperresponsiveness and airflow obstruction in asthma [6][7][8]. ADMA is an endogenous inhibitor of all isoforms of NOS and is produced by the methylation of L-arginine residues by protein methyltransferases.…”
mentioning
confidence: 99%
“…Additionally, exogenous administration of ADMA to lung epithelial cells in vitro has been demonstrated to lead to uncoupling of NOS, resulting in the formation of superoxide [72]. Furthermore, chronic (2-week) exogenous administration of ADMA to mice resulted in increased arginase activity, collagen deposition and increased airways responsiveness to methacholine [78]. Further studies from the same group have recently shown that infusion concurrent with an ovalbumin sensitization and challenge regimen potentiates allergic inflammation [79].…”
Section: Endogenous Nos Inhibition and L-arginine Metabolismmentioning
confidence: 99%